Mangrove Crab (Scylla spp.) Catching Units as a Community Side Business in Tarakan Tengah Sub-District , City of Tarakan - Hidayat, Nur; Amiluddin, Amiluddin; Baso, Aris (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2022)
Tarakan City is one of the areas that has considerable fishery potential, one of which is mud crabs, based on the results of a survey in 2018 Tarakan City has exported 4,500 tons of mud crabs per year. This encourages the emergence of mangrove crab fishing as a side business that can increase people's income and welfare. The purpose of this study was to analyze the costs, revenues, revenues and business feasibility and marketing of mud crabs. This research was conducted from March to April 2021. The method used was descriptive qualitative and quantitative using a questionnaire. The sampling method used is the cluster sampling method with a total sample of 36 people, consisting of 25 mud crab catchers, 6 collectors, 3 small traders and 2 large traders. Analysis of the data used is profit analysis and marketing analysis. The results showed that the profit of the mud crab catcher was IDR 5,796,296 per month with an income of IDR 8,375,600 per month and a total cost of IDR 2,579,305 per month, with an R/C value of 3.25 or feasible to run. The highest marketing margin is found in the marketing agency of collecting traders, which is IDR 20,000 and the lowest margin is found in marketing channel 1 at the small and large trader institution of IDR 10,000. The highest marketing costs incurred by marketing agencies are in marketing channel 3, which is IDR 34,436, the most efficient marketing agency is small traders in marketing channel 1 with an average marketing efficiency value of 0.03%.